Validation of a Point-of-Care Ferritin Card Test Against Venous Sampling for the Diagnosis of Iron Deficiency and Iron Deficiency Anaemia in Low- and Middle-Income Countries - Divakar, Hema; Joshi, Sheetal; Singh, Rita; Narayanan, Poorni; Gv, Divakar (British Journal of Healthcare and Medical Research, 2025)
Objective: Iron deficiency (ID) and iron deficiency anaemia (IDA) remain pervasive health issues in low- and middle-income countries (LMICs), with significant implications for maternal health. This study aimed to validate a qualitative point-of-care (POC) ferritin card test against standard venous ferritin estimation for detecting ID and IDA, and to assess its role in guiding injectable iron therapy in resource-limited settings. Methods: We enrolled 75 women aged 14–62 years, each undergoing haemoglobin (Hb) testing, venous ferritin estimation (laboratory-based), and POC ferritin card testing using a finger-prick sample. Hb <9 g/dL was the threshold for initiating injectable iron therapy under standard protocol, while ferritin <30 ng/mL was considered indicative of depleted stores. The POC device was validated for specificity, sensitivity, and repeatability using known QC standards from the manufacturer’s Certificate of Analysis. Results: Hb testing alone identified 13/75 (17.3%) women as candidates for injectable iron therapy. Ferritin testing detected an additional 24/75 (32.0%) women with depleted stores despite normal Hb, increasing the total eligible for treatment to 37/75 (49.3%). The POC card test demonstrated strong concordance with venous ferritin across predefined cut-off ranges. Operational benefits included rapid turnaround time (<5 minutes), no electricity requirement, and low per-test cost. Conclusion: The POC ferritin card test reliably detects iron deficiency in women with normal Hb, substantially increasing the number identified for early intervention. Its integration into maternal health screening in LMICs could significantly improve outcomes by enabling timely treatment.